William. M. Caswell, Revised Charter and Compiled Ordinances and Resolutions of the City of Los Angeles 85 (1878) - (:unkn) unknown (My University, 1878)
Ordinance 36: Prohibited the carry of any dirk, pistol, sword-cane, slung-shot, or other dangerous or deadly weapon within the corporate limits of the city of Los Angeles. Violators fined not more than one hundred dollars, and imprisoned at the discretion of the mayor not to exceed ten days.
Keywords: CARRY